Evaluating the sustainability of agritourism in the wild coast region of South Africa - Priviledge Cheteni; Ikechukwu Umejesi (Cogent Economics & Finance, 2023)
In recent decades, agritourism has been proposed by various agencies as a strategy for the sustainable development of rural areas and the diversification of the rural economy. The study aimed to examine and identify the role of agritourism in entrepreneurship and sustainability. Semi-structured interviews were used to collect data from 15 business owners and 68 residents from local households on the Wild Coast. Consequently, various facets of agritourism for sustainable rural development were investigated using a qualitative research method. The findings revealed that agritourism in the study area can be enhanced by integrating it with farm entrepreneurship. Furthermore, because many disenfranchised families already engage in crafts, subsistence farming, fishing, and other activities, agritourism has the potential to lift many of them out of poverty.
Keywords: 330; agritourism; ecosystem; entrepreneurship; environment; rural development